Chemistry of the Redox Series from Hexahydroxybenzene to Cyclohexanehexaone - Hettegger, Hubert; Hosoya, Takashi; Rosenau, Thomas (Current Organic Synthesis, 2016)
Six-electron oxidation of hexahydroxybenzene C6(OH)6 leads to cyclohexanehexaone (CO)6 via two intermediates, tetrahydroxy-1,4-benzoquinone and rhodizonic acid (5,6-dihydroxycyclohex-5-ene-1,2,3,4-tetraone). All these quinoid compounds show a rich and colorful chemistry: formation of chromophoric metal complexes is a special feature of the compounds, which have been employed as specific reagents for metal ions. The formation of colored complexes even with alkali and earth alkali metal ions – not only with transition-metal ions – is a peculiarity. The derivatization of hydroxyl and oxo-functions proceeds as expected, but is superimposed by complex tautomerism between ortho-quinoid and para-quinoid counterparts as well as formation of hydrates of the keto functionalities. The generation of aromatic anions is a special feature of the compounds, its many implications having rendered them favorite objects of study for theoretical and computational chemists. Dimerization, ring contraction and decarbonylation processes are another class of pathways which offer a wide field for mechanistic studies. The general chemistry of the compound series from hexahydroxybenzene to cyclohexanehexaone is reviewed, focusing on reactions, mechanisms and derivatizations along with some important structural and analytical features.
Keywords: tetrahydroxy-1